Effects of Apigenin on Experimental Ischemia/Reperfusion Injury in the Rat Ovary - Zeynep Soyman1; Sefa Kelekçi2; Veysel Sal3; Osman Şevket4; Nihan Bayındır5; Hafize Uzun6 (Balkan Medical Journal, 2017)
Background: Apigenin is a plant-derived compound belonging to the flavone class, which possess antioxidant, free-radical-scavenging and anti-inflammatory properties. Aims: To address the effects of apigenin on serum anti-mullerian hormone levels, tissue oxidative stress parameters and histopathological changes in ovarian ischemia/reperfusion injury. Study Design: Animal experiment. Methods: Twenty-eight female Wistar albino rats were randomly separated into four sections: Sham operation (group 1), ischemia/reperfusion plus saline (group 2), ischemia/reperfusion plus dimethyl sulfoxide (group 3) and ischemia/reperfusion plus apigenin (group 4). In all ischemia/reperfusion groups, a bilateral adnexal 3-h period of ischemia was performed, followed by 3-h of reperfusion. A single dose of 15 mg/kg apigenin was given intraperitoneally 60 min before reperfusion in group 4. After 3-h of reperfusion, both ovaries were removed, and blood samples were collected. The main outcome measures were serum anti-mullerian hormone levels, ovarian tissue malondialdehyde, total nitric oxide, Cu/Zn superoxide dismutase, catalase and glutathione levels and histopathological damage scores. Results: The ovarian tissue nitric oxide level was significantly lower, and the glutathione level was significantly higher in group 4 compared with groups 2 and 3. There was no significant difference in anti-mullerian hormone levels among the three ischemia/reperfusion groups. The histopathological damage score was lower in group 4 than in groups 2 and 3 (p>0.05). Conclusion: Administration of apigenin has no significant protective effect on ovarian reserve and tissue damage in ovarian ischemia/reperfusion injury